2016
DOI: 10.1002/dmrr.2843
|View full text |Cite
|
Sign up to set email alerts
|

Glycated albumin and ratio of glycated albumin to glycated hemoglobin are good indicators of diabetic nephropathy in type 2 diabetes mellitus

Abstract: Background We investigated the association between serum levels of glycated albumin (GA),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…In all, 24 articles 9 , 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 with a total of 3928 patients with CKD were eventually identified according to the search strategy and the inclusion and exclusion criteria. Characteristics and other information extracted from each publication are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 24 articles 9 , 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 with a total of 3928 patients with CKD were eventually identified according to the search strategy and the inclusion and exclusion criteria. Characteristics and other information extracted from each publication are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity was still present in the included subjects due to the different CKD status, so we performed a subgroup analysis and made a comparison of GA and HbA1c in different CKD stages. Two studies 37 , 39 were subsequently excluded from subgroup analysis, because these studies provided only an overall R value to represent the correlation coefficient in different CKD stages. There were a total of 96 patients in early stages of CKD and 3731 patients in advanced CKD.…”
Section: Resultsmentioning
confidence: 99%
“…It is more suitable for monitoring short‐term diseases of diabetes . Correlation between GA concentration and GA to HbA 1c ratio with severity of diabetic retinopathy (DR) has been reported in patients with type 2 diabetes mellitus . However, there are limited studies to investigate the association between GA concentration and GA to HbA 1c ratio with DR in prediabetic patients in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2016) studied 206 types 2 DM patients in China and found a similar serum GA level with the Taiwan study, which is 17,9 (5,9) %. Characteristic of the patient in both studies are identical [18], [22].…”
Section: Serum Glycated Albumin Level In Type 2 Dm Patientsmentioning
confidence: 91%